Capital Share Risk in U.S. Asset Pricing - LETTAU, MARTIN; LUDVIGSON, SYDNEY C.; MA, SAI (Journal of Finance, 2019)
ABSTRACT A single macroeconomic factor based on growth in the capital share of aggregate income exhibits significant explanatory power for expected returns across a range of equity characteristic portfolios and nonequity asset classes, with risk price estimates that are of the same sign and similar in magnitude. Positive exposure to capital share risk earns a positive risk premium, commensurate with recent asset pricing models in which redistributive shocks shift the share of income between the wealthy, who finance consumption primarily out of asset ownership, and workers, who finance consumption primarily out of wages and salaries.